High yield process for the production of active human alpha-Galactosidase A in CHO-K1 cells through lentivirus transgenesis - Rodríguez, María Celeste (2017)
Fabry disease is an X-linked recessive disorder caused by a deficiency in lysosomal α-Galactosidase A. Currently, two enzyme replacement therapies (ERT) are available. However, access to orphan drugs continues to be limited by their high price. Selection of adequate high-expression systems still constitutes a challenge for alleviating the cost of treatments. Several strategies have been implemented, with varying success, trying to optimize the production process of recombinant human α-Galactosidase A (rhαGAL) in Chinese hamster ovary (CHO-K1) cells. Herein, we describe for the first time the application of a strategy based on third-generation lentiviral particles (LP) transduction of suspension CHO-K1 cells to obtain high-producing rhαGAL clones (3.5 to 59.4 pg.cell-1.d-1). After two purification steps, the active enzyme was recovered (2.4 x 106 U.mg-1) with 98% purity and 60% overall yield. Michaelis-Menten analysis demonstrated that rhαGAL was capable of hydrolyzing the synthetic substrate 4MU-α-Gal at a comparable rate to Fabrazyme®, the current CHO-derived ERT available for Fabry disease. In addition, rhαGAL presented the same mannose-6-phosphate (M6P) content, about 40% higher acid sialic amount and 33% reduced content of the immunogenic type of sialic acid (Neu5Gc) than the corresponding ones for Fabrazyme®. In comparison with other rhαGAL production processes reported to date, our approach achieves the highest rhαGAL productivity preserving adequate activity and glycosylation pattern. Even more, considering the improved glycosylation characteristics of rhαGAL, which might provide advantages regarding pharmacokinetics, our enzyme could be postulated as a promising alternative for therapeutic use in Fabry disease.